Pembuatan Hidroponik Sistem Nutrient Film Technique (NFT) dengan Memanfaatkan Limbah Botol Plastik untuk Tanaman Pakcoy di Dusun Nunggal II Desa Dakung Kabupaten Lombok Tengah - Aziz, Faizul Bayani; Harisanti, Baiq Muli; Primawati, Sri Nopita; Jannah, Husnul; Masiah, Masiah; Mursali, Saidil; Utami, Septiana Dwi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Packaging waste for products or goods that are no longer used can still be recycled into goods that are useful and economically valuable. In general, inorganic waste is very difficult to decompose naturally. The problem of increasing waste volumes needs to be handled wisely so that environmental pollution can be avoided, especially inorganic waste in the form of plastic bottles. The state of society in handling waste, especially plastic bottles, is still very low. One way that can be done is by providing education and direct assistance to the public regarding techniques for managing inorganic waste, especially used bottles or other plastic containers into more useful products. Utilizing used bottles as a medium for hydroponic plants is an effective way to raise public interest and awareness about the importance of managing plastic bottle waste. This activity is also a means of learning and motivating the community about hydroponic business opportunities using plastic bottles. Apart from that, this can be a very productive alternative activity for society.